Questão agrária e territórios em disputa: embates políticos entre agronegócio e agricultura camponesa/familiar na década de 2000 - Ribeiro, Raphael Medina (2009)
The elements that bring out the agrarian question in Brazil at the threshold of a century show that there are conflicts between two social kinds, economic and political, that reproduce historically in the field, following the capitalist uneven logic contradictory development: they are known at the moment by the agribusiness (capitalist agriculture) and peasantry/family farming. This research aimed to understand the political dimension of conflicts and territorial disputes between these two development models, especially the spaces, territories and social actors present in the civil society and the state. The methodological approach used consisted of a bibliographic study, documentary research (press reports, documents of civil society organizations, state bodies and other materials); direct observation of political practices and speeches in public arena; and semi-structured interviews. It was noticed, therefore, the diversity of social actors who protagonist the agrarian question in this decade in the spheres of civil society and State, as well as features of their presence and performance in the national political sphere. The executive and legislative federal powers were recognized as rich institutional spaces for an analysis of political struggle between agribusiness and peasantry/family farming, in which we highlight instances and actors/partners closer to the agricultural demands (among them, the rural caucus and Núcleo Agrário do Partido dos Trabalhadores). In the midst of these conflicts, the political action of rural social movements against the agribusiness development model, such as those linked to the Via Campesina in Brazil - among whom the Movimento dos Trabalhadores Sem-Terra get relief it also appears as an important element of analysis, the demarcation lines on the agrarian question from the perspective of the disputed territories.